Topical application of Chinese herbal medicine DAEP relieves the osteoarthritic knee pain in rats - Wing Sum Siu; Wai Ting Shum; Wen Cheng; Chun Wai Wong; Hoi Ting Shiu; Chun Hay Ko; Ping Chung Leung; Christopher Wai Kei Lam; Chun Kwok Wong (BMC, 2019)
Abstract Background The potential adverse effects of conventional oral pharmacotherapy of osteoarthritis (OA) restrict their long-term use. Topical application of a Chinese herbal paste for relieving OA knee pain can be effective and safe. However, evidence-based scientific research is insufficient to support its application worldwide. The aim of this study was to investigate the in vivo efficacy of a topical Chinese herbal paste on relieving OA knee pain and its underlying mechanism. Methods An OA rat model was developed by anterior cruciate ligament transection (ACLT) followed by treadmill running. A herbal paste including Dipsaci Radix, Achyranthis Bidentatae Radix, Eucommiae Cortex and Psoraleae Fructus, named as DAEP, was applied topically on the knee joint of the rats (DAEP). The rats without DAEP treatment served as Control. Rats with surgery but without ACLT, treadmill running and DAEP treatment acted as Sham. The morphologic change of the knee joint was observed radiographically. Nociception from the knee of the rats was assessed using Incapacitent test and CatWalk gait system. The therapeutic mechanism was investigated by analyzing the gene and protein expression of inflammatory markers via qPCR and Western blot, respectively. Results Radiographic images showed less destruction at the posterior tibial plateau of the DAEP group compared with the Control after 2 weeks of treatment. The static weight ratio and the gait parameters of the Control were reduced significantly via Incapacitance test and CatWalk gait analysis, respectively. DAEP treatment increased the Print Area and Maximum Intensity significantly compared with the Control. DAEP significantly suppressed the upregulation of gene expression of interleukin (IL)-6, tumor necrosis factor (TNF)-α, and inducible nitric oxide synthase (iNOS). Conclusions DAEP exhibited its effect via the nuclear factor (NF)-κB pathway by suppressing the phosphorylation of IκB kinase αβ (p-IKKαβ) and cyclooxygenase-2 (COX-2) protein expression. This study provides scientific evidence to support the clinical application of the Chinese herbal paste on reliving OA pain.